Trajectories of peasant women: the struggle for education - Elizabeth Moreira Gomes (Universidade Federal do Norte do Tocantins, 2021)
This article is a reinterpretation of the research implemented in the doctoral process in which the social representations of 'writing' of undergraduate students in the rural education was studied. Curso Linguagens e Códigos da Universidade Federal dos Vales do Jequitinhonha e Mucuri (UFVJM). In the thesis, narrative interviews were conducted with a group of 15 undergraduates in order to understand their relationships/conceptions of writing. Then, it was possible to notice the importance of the female figure in the fight for a free, high quality rural education. Mothers, wives, girlfriends, were widely mentioned as having decisive roles in students entering as well as their remaining in the undergraduate course. Thus, it was from the narrative interviews that a question has been posed, and has, in the space of this article, an opportunity for reflection. If women are the ones encouraging their partners, children, brothers, to further their studies, how do such women organize themselves so that they too can study? What is the necessary support so that such women can 'leave home'? From a methodological point of view, two testimonies from young women coming from different backgrounds were selected.